The Design and Implementation of a Digital Magnetic Tape System and its Application in Radio-Isotope Scanning - Blum, Leon Stephen (My University, 1972)
This thesis is divided into two general sections. The first deals with the theory of digital magnetic recording and surveys the more common techniques used in digital magnetic tape recording. A new recording format is described which leads to a greater data rate at normal recording densities. The design and implementation of a recording system using this technique is described. The second section outlines the design of a portable digital recording system compatible with the peripheral unit described in section 1. The application of this system to the acquisition of data from a radioisotope scanner used in nuclear medicine is described and some basic results obtained from the system are demonstrated. Fundamental work towards image enhancement is outlined.
Keywords: digital magnetic tape recording; image enhancement